2015
DOI: 10.5430/ijfr.v6n2p190
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Fiscal Policy Operations on Stock Price Performance: Empirical Evidence from Nigeria

Abstract: This paper examines the relationship between Government fiscal policy measures and stock prices in Nigeria during the period 1985 -2012. Employing OLS, co-integration, error correction mechanism (ECM), Granger Causality and impulse response and variance decomposition techniques on fiscal policy -stock prices model patterned after a multivariate regression, the study found a significant and negative impact of Public expenditure on stock prices, while Government Domestic Debt Outstanding exerts a significant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…Although literature on the effect of public debt on securities market returns is still lean, this finding agrees with [40] in Kenya. In contrast this finding differed with the finding of [28] in the European Union, and [41] in Nigeria's securities market who found that public debt had a positive influence on stock prices. Table 10 presents the results of the determination of the moderating effect of public debt on the effect of inflation rate on securities market returns against the null hypothesis that public debt does not statistically significantly moderate the effect of inflation rate on securities market returns at the Nairobi Securities Exchange, that is, .…”
Section: Effect Of Public Debt On Securities Market Returnscontrasting
confidence: 99%
See 1 more Smart Citation
“…Although literature on the effect of public debt on securities market returns is still lean, this finding agrees with [40] in Kenya. In contrast this finding differed with the finding of [28] in the European Union, and [41] in Nigeria's securities market who found that public debt had a positive influence on stock prices. Table 10 presents the results of the determination of the moderating effect of public debt on the effect of inflation rate on securities market returns against the null hypothesis that public debt does not statistically significantly moderate the effect of inflation rate on securities market returns at the Nairobi Securities Exchange, that is, .…”
Section: Effect Of Public Debt On Securities Market Returnscontrasting
confidence: 99%
“…Other studies, [39] and [40], also found that public debt's effect on the securities market was insignificant in Nigeria and Kenya respectively, although the effect was negative in Kenya [40]. Assessment of the impact of public debt on Nigeria's securities market [41] found that it had a significant and positive influence on stock prices.…”
Section: Public Debt and Securities Market Returnsmentioning
confidence: 95%
“…From the ARDL result in Tables 11 -13, government total expenditure was found to be positively related to stock market development indices (market capitalization ratio, the value of stock traded ratio, and turnover ratio) in line with a priori expectation of a positive linkage. This supports the works of Perveen and Rahman (2018), Onyema (2017), Ali, Zaman, Ziaei, and Anuar (2014) but disagreed with of Ogbulu, Torbira, and Umezinwa (2015), Hsing (2013) and Anghelache, Jakova, and Oanea (2016) on the negative association between government expenditure and development in the stock market. Conventionally, when the government increases its recurrent spending, there would be more funds in the hands of the citizen.…”
Section: Resultssupporting
confidence: 81%
“…Studies on fiscal policy and stock market performance as well as stock market returns have been undertaken by various researchers in Nigeria (see Prukumpai & Sethapramote, 2019;Nwaogwugwu, 2018;Eyo, 2018;Perveen & Rahman, 2018;Onyema, 2017;Kuncoro, 2017;Anghelache, Jakova & Oanea, 2016;Ogbulu, Torbira & Umezinwa, 2015;Ali, Zaman Ziaei & Anuar, 2014;Mutulis & Olweny, 2018;Gowriah, Seetanah, John & Keshav, 2014;Cheng & Sun, 2013;Hsing, 2013;Bekhet & Othman, 2012;Osamwonyi & Evbayiro-Osagie, 2012). However, about stock market development using the World Bank (2013) indices of measuring development in the stock market (stock market capitalization ratio, the value of stock traded ratio, and turnover ratio) have often been ignored in studies conducted in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have studied the effects of fiscal policy on stock return (Ogbulu, Torbira, & Umezinwa, 2015;Anghelache, Jakova, & Oanea, 2016) as well as monetary policy on stock returns (Uwubanmwen & Eghosa, 2015). However, few researchers studied the combined effects of the two policies on stock returns especially in the Nigeria context (Abata et al, 2012;Gowriah et al, 2014;Nwaogwugwu & Evans, 2016;Nwakoby & Alajekwu, 2016;Lawal, Somoye, Babajide, & Nwanji, 2018;Nwaogwugwu, 2018) Researchers are equally divided, whether expansionary or contractionary, inflationary, or disinflationary fiscal and monetary policies have a negative, positive, or non-statistically significant relationship with stock market performance.…”
Section: Introductionmentioning
confidence: 99%